Myocardial lipid content in Fabry disease: a combined 1H-MR spectroscopy and MR imaging study at 3 Tesla. Issue 1 (December 2016) - Petritsch, B.; Köstler, H.; Weng, A.; Horn, M.; Gassenmaier, T.; Kunz, A.; Weidemann, F.; Wanner, C.; Bley, T.; Beer, M.
Abstract Background Fabry disease is characterized by a progressive deposition of sphingolipids in different organ systems, whereby cardiac involvement leads to death. We hypothesize that lysosomal storage of sphingolipids in the heart as occurring in Fabry disease does not reflect in higher cardiac lipid concentrations detectable by1 H magnetic resonance spectroscopy (MRS) at 3 Tesla. Methods Myocardial lipid content was quantified in vivo by1 H-MRS in 30 patients (12 male, 18 female; 18 patients treated with enzyme replacement therapy) with genetically proven Fabry disease and in 30 healthy controls. The study protocol combined1 H-MRS with cardiac cine imaging and LGE MRI in a single examination. Results Myocardial lipid content was not significantly elevated in Fabry disease (p = 0.225). Left ventricular (LV) mass was significantly higher in patients suffering from Fabry disease compared to controls (p = 0.019). Comparison of patients without signs of myocardial fibrosis in MRI (LGE negative;n = 12) to patients with signs of fibrosis (LGE positive;n = 18) revealed similar myocardial lipid content in both groups (p > 0.05), while the latter showed a trend towards elevated LV mass (p = 0.076). Conclusions This study demonstrates the potential of lipid metabolic investigation embedded in a comprehensive examination of cardiac morphology and function in Fabry disease. There was no evidence that lysosomal storage of sphingolipids influences cardiac lipid content as measured by1 H-MRS. Finally, the authors share the opinion that a comprehensive cardiac examination including three subsections (LGE;1 H-MRS; T1 mapping), could hold the highest potential for the final assessment of early and late myocardial changes in Fabry disease.